Parametric investigation of optimum thermal insulation thickness for external walls - Uludağ Üniversitesi/Mühendislik Fakültesi/Makine Mühendisliği Bölümü.; Kaynaklı, Ömer; 8387145900 (Energies, 2011)
Numerous studies have estimated the optimum thickness of thermal insulation materials used in building walls for different climate conditions. The economic parameters (inflation rate, discount rate, lifetime and energy costs), the heating/cooling loads of the building, the wall structure and the properties of the insulation material all affect the optimum insulation thickness. This study focused on the investigation of these parameters that affect the optimum thermal insulation thickness for building walls. To determine the optimum thickness and payback period, an economic model based on life-cycle cost analysis was used. As a result, the optimum thermal insulation thickness increased with increasing the heating and cooling energy requirements, the lifetime of the building, the inflation rate, energy costs and thermal conductivity of insulation. However, the thickness decreased with increasing the discount rate, the insulation material cost, the total wall resistance, the coefficient of performance (COP) of the cooling system and the solar radiation incident on a wall. In addition, the effects of these parameters on the total life-cycle cost, payback periods and energy savings were also investigated.